Show that log base b a . log base c b .log base a c = 1
Answers
Answered by
1
Answer:
LHS = log a base b . log b base c .log c base a
RULE :
log x base b = log x base c / log b base c
LHS =( log a base c / log b base c ) . log b base c .log c base a
= log a base c .log c base a
RULE :
log a base b = 1/ log b base a
LHS = log a base c . 1/ log a base c
= 1 = RHS
HENCE PROVED
if the asnwer is useful pls mark as brainliest.....plss
Answered by
0
bro quesion very hard bero chill maro bero
Similar questions